2014
DOI: 10.7498/aps.63.197101
|View full text |Cite
|
Sign up to set email alerts
|

First principles calculation of occupancy, bonding characteristics and alloying effect of Cr, Mo, Ni in bulk α-Fe?

Abstract: Variations of electronic properties of bulk α-Fe(C) due to the addition of Cr, Mo, Ni are studied using the first principles method, which is based on the density functional theory (DFT). Lattice distortion, cohesive energy, density of states, Mulliken charge population, overlap population and charge density differences are calculated by the generalized gradient approximation (GGA)-PW91, and the occupancy, bonding characters and alloying effect of α-Fe(C) after mixing with alloy atoms are explained. Results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The wider the pseudogap, the stronger the covalent bond. [ 58 ] Table 7 shows the size of the pseudogap of the density of states of these four MEAs. It can be seen from the table that the order of the pseudogap of these four alloys is TiNbTaHf>TiNbHfZr>TiHfTaZr>TiNbTaZr.…”
Section: Resultsmentioning
confidence: 99%
“…The wider the pseudogap, the stronger the covalent bond. [ 58 ] Table 7 shows the size of the pseudogap of the density of states of these four MEAs. It can be seen from the table that the order of the pseudogap of these four alloys is TiNbTaHf>TiNbHfZr>TiHfTaZr>TiNbTaZr.…”
Section: Resultsmentioning
confidence: 99%
“…By comparison, it was found that the energy of each corrosive ion was the lowest at the bridge site of the TiO 2 (100) surface. If the energy of the adsorption system were more negative, its structure would be more stable [16]. Therefore, it can be determined that all of the best adsorption sites of Cl − , HS − , S 2− , HCO 3 − , and CO 3 2− on the TiO 2 (100) surface were bridge sites.…”
Section: Stable Adsorption Modelmentioning
confidence: 99%
“…在这些计算模拟方法中, 第一 性原理方法能够对掺杂体系的电子结构、力学性 能、成键形态、结构稳定性等进行准确模拟, 从而 在原子尺度上实现对缺陷元素和氢元素相互作用 的理论诠释. 例如, Chatterjee等 [8] 对FeNi合金 在Ni元素不同掺杂浓度、不同掺杂位置下的相对 稳定性进行了基于DFT+U的计算分析, 发现Ni 掺杂bcc结构Fe的稳定性关键取决于Ni在Fe基 体中的分布状态; Xiong等 [9] 通过计算H原子在 bcc-Fe(1 0 0)表面以及不同元素掺杂后表面的吸 附和渗透过程, 指出Mn, Cr, V元素掺杂形成合金 表面后能降低H原子的吸附稳定性与覆盖率, 是 抑制H元素渗透的理想合金掺杂元素. 文平等 [10] 探讨了合金钢中Cr, Mo, Ni原子与铁素体α-Fe(C) 的作用, 发现Cr能够强化晶胞并增强体系的稳定 性, 对增强铁素体机械性能帮助较大; Mo虽然能 强化晶胞, 但其强烈的反键作用却使晶胞的稳定性 大大降低.…”
unclassified